Marital therapy help-seeking attitudes of young adults in mainland China - Adams, Rebekah D.; Aducci, C. J.; Anderson, Jared R.; Johnson, Matthew D.; Zheng, Fuming; Liu, Wenli (My University, 2013)
Using qualitative interview data from young adults in Mainland China (n = 24), the current study explored help-seeking attitudes toward marital therapy. In general, significant relationship problems that participants labeled as communication difficulties, emotional distance, and thoughts of divorce were seen as legitimate reasons to seek out marital therapy. Nearly all participants reported that before seeking out professional services, they would first talk to friends and family members, and only if problems did not abate or continued to be a significant risk to relationship harmony and stability would they be open to seeking out professional services. Finally, the participants generally believed that their family and friends would support their decision to access marital therapy services. The results from this study point to the importance of developing effective, culturally relevant approaches to the treatment of marital distress in Mainland China.
Keywords: China; Marital therapy